A novel homozygous ERCC5 truncating mutation in a family with prenatal arthrogryposis—Further evidence of genotype–phenotype correlation. Issue 7 (3rd April 2014) - Drury, Suzanne; Boustred, Christopher; Tekman, Mehmet; Stanescu, Horia; Kleta, Robert; Lench, Nicholas; Chitty, Lyn S.; Scott, Richard H.
<x xml:space="preserve">Abstract</x> We report on a family with five fetuses conceived to first cousin parents presenting with abnormal ultrasound findings including contractures and microcephaly. Cerebellar hypoplasia and ventriculomegaly were also present in two and fetal edema developed in the one fetus that survived beyond 24 weeks of gestation. Linkage studies of 15 members of the family, including four affecteds, were undertaken followed by exome sequencing of one affected individual and their parents. Analysis of exome data was restricted to the 9.3 Mb largest shared region of homozygosity identified by linkage; a single novel homozygous mutation in the proband that was heterozygous in the parents (ERCC5 c.2766dupA, p.Leu923ThrfsX7) was identified. This segregated with disease. ERCC5 is a component of the nucleotide excision repair machinery and biallelic mutations in the gene have previously been associated with xeroderma pigmentosum (group G), Cockayne syndrome and the more severe cerebrooculofacioskeletal syndrome. The phenotype in the family we report on is consistent with a severe manifestation of cerebrooculofacioskeletal syndrome. Our data broaden the reported clinical spectrum of ERCC5 mutations and provide further evidence of genotype–phenotype correlation with truncating mutations being associated with severe phenotypes. They also demonstrate the molecular diagnostic power of a combined approach of linkage studies and exome sequencing in families with rare, genetically heterogeneous disorders and a well described pedigree. © 2014 Wiley Periodicals, Inc.